1976
DOI: 10.1017/s0022172400055108
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the effect of contact with environmental mycobacteria on the pattern of sensitivity to a range of new Tuberculins amongst Ugandan adults

Abstract: A range of new Tuberculins prepared from extracts of living organisms belonging to 12 mycobacterial species has been used to assess the effect of BCG immunization and contact with environmental mycobacteria on Ugandan adults. A total of 2,456 tests were carried out on 562 people, 86% of whom came from three areas selected for special study. These areas were chosen on the basis of occurrence of leprosy and M. ulcerans infection and on data concerning the distribution of environmental mycobacteria. It was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Skin tests with a soluble new tuberculin called Vaccin prepared from Myco. vaccae showed that people living in the environment from whence it was cultured reacted to it (Stanford et al 1976). Such sensitization may have primed the immune system for effective BCG vaccination (Stanford et al 1981a).…”
Section: Introductionmentioning
confidence: 99%
“…Skin tests with a soluble new tuberculin called Vaccin prepared from Myco. vaccae showed that people living in the environment from whence it was cultured reacted to it (Stanford et al 1976). Such sensitization may have primed the immune system for effective BCG vaccination (Stanford et al 1981a).…”
Section: Introductionmentioning
confidence: 99%
“…This may be partially responsible for the high proportion of new herd breakdowns identified in cattle tuberculosis control measures, where up to 60% of slaughtered animals have no visible lesions and are negative on culture (Wilesmith et al 1982). However, the greatest importance of environmental mycobacteria is believed to be their role in the immunological priming of humans and animals, thereby modifying their immune response to subsequent exposure to pathogenic species or to Mycobucterium bovis BCG (Stanford et al 1976;Shield 1983;Pallen 1984;Brown et al 1985;Grange 1986Grange , 1987Lyons and Naafs 1987;Stanford et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…They have been used in studies of leprosy (Paul, Stanford & (Carswell, 1975) and Mycobacterium ulcerans infection (Stanford, Revill, Gunthorpe & Grange, 1975), and have also been used to measure the effect of BCG immunization and of geographical locality on both school children (Paul, Stanford, Misljenovic & Lefering, 1975) and adults (Stanford et al 1976). In J. L. STANFORD AND OTEERS to environmental mycobacteria was found among the school children coming from the desert regions of Lodwar in Kenya and Karamoja in Uganda (not published).…”
Section: Introductionmentioning
confidence: 99%